Integration of Public Relations Values in KiaiKanjeng Cultural Da'wah Communication on the CakNun.com Youtube Channel - Nuhaza, Irma; Ghoni, Abdul; Eken, Metin; Adeni, Adeni (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study aims to analyze the integration of public relations values in cultural da'wah communication in the digital era carried out by the KiaiKanjeng music group through the CakNun.com YouTube channel. As a cultural arts group associated with Emha Ainun Nadjib (CakNun), KiaiKanjeng uses the medium of music and culture to convey inclusive, humanist, and dialogical Islamic messages. In the context of digital space, the da'wah they build is not only informative, but also forms communication relations with the public. This research uses a descriptive qualitative approach with content analysis techniques to identify da'wah themes, as well as media content studies to interpret symbols, visuals, and cultural meanings contained in KiaiKanjeng videos. Data was obtained from a number of videos selected with a focus on this research that highlights how public relations values such as credibility, honesty, consistency, and two-way communication are integrated in their da'wah narratives. CakNun.com's YouTube channel is positioned as a strategic medium to build a culturally friendly Islamic image, respond to contemporary issues, and strengthen emotional bonds with digital audiences. The results show that the integration of public relations values is the key to KiaiKanjeng's success in delivering relevant, communicative, and adaptive da'wah messages to a plural society in the digital era. This study contributes to the study of Islamic Communication and Broadcasting in relation to the integration of public relations values to cultural da'wah activities.